Challenges of Teaching Technical Vocabulary at University Level - Sahin, Mehmet; Haslinda, Hashim (INTI International University College, 2007)
This paper is based on a comparative study into the challenges of teaching technical vocabulary encountered while teaching at a Technical Science College in Turkey and at Universiti Malaysia Pahang, Malaysia. It is a fact that delivering technical terms in English poses some difficulties to the teachers. Some of these obstacles stem from the task inside classroom itself as a specific point in teaching language field. The second comes from teachers as they are generally less productive to present the vocabulary items in the event of encountering teaching complications. Some problems arise from learners themselves as they generally fall behind of essential language level or they lack motivation. This paper aims (a) to analyse the challenges of teaching technical vocabulary from teachers’ perspectives, (b) analyse them in terms of syllabus design, and (c) render some recommendations towards stakeholders in order that they should take all these barriers into account while designing their curricula